2022
DOI: 10.3390/ijms231911831
|View full text |Cite
|
Sign up to set email alerts
|

Aggregatibacter actinomycetemcomitans Cytolethal Distending Toxin-Induces Cell Cycle Arrest in a Glycogen Synthase Kinase (GSK)-3-Dependent Manner in Oral Keratinocytes

Abstract: Cytolethal distending toxins (Cdt) are produced by a diverse group of pathogens. One Cdt-producing organism, Aggregatibacter actinomycetemcomitans, plays a critical role in the pathogenesis of a unique form of periodontitis, formerly referred to as localized aggressive periodontitis. The active Cdt subunit, CdtB, is a potent phosphatidylinositol (PI) 3,4,5-triphosphate phosphatase capable of inducing PI-3-kinase signaling blockade, a requisite for Cdt-induced toxicity in lymphocytes. In this study, we extended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 89 publications
2
13
0
Order By: Relevance
“…Primary human gingival keratinocytes (PGK) were derived from discarded healthy gingival tissue obtained from patients undergoing crown lengthening procedures as previously described [ 39 , 41 ]. Briefly, tissue was washed in a HAMS F12 nutrient mixture (ThermoFisher Scientific, Waltham, MA, USA) containing 1% penicillin/streptomycin and 1% ampthotericin and then cut into 0.3 cm 2 fragments.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Primary human gingival keratinocytes (PGK) were derived from discarded healthy gingival tissue obtained from patients undergoing crown lengthening procedures as previously described [ 39 , 41 ]. Briefly, tissue was washed in a HAMS F12 nutrient mixture (ThermoFisher Scientific, Waltham, MA, USA) containing 1% penicillin/streptomycin and 1% ampthotericin and then cut into 0.3 cm 2 fragments.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we demonstrated that oral-epithelial cells (OE) are unique in their response to Aa Cdt [ 39 ]. Assessment of the effect of Aa Cdt on two immortalized OE lines as well as primary gingival keratinocytes (PGKs) showed that all three cell types were sensitive to Aa Cdt-induced cell cycle arrest as toxin-treated cells accumulated in the G2/M phase within 24 h of exposure to low Cdt concentrations (pg/mL) [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These substances are also known as genotoxins, including cytolethal distending toxin (CDT), typhoid toxin (TT) and colibactin ( Wang and Li, 2022 ). CDT was the first described bacterial genotoxin and encodes three polypeptides (CdtA, CdtB, and CdtC) ( Shenker et al., 2022 ). CDT induces double-strand breaks (DSBs), activates the ataxia telangiectasia mutated (ATM)-dependent DNA damage response and forms DNA repair complexes, triggering irreversible G2/M arrest of the cell cycle and apoptosis ( Lara-Tejero and Galán, 2000 ; Zhang et al., 2018 ; Tatekawa et al., 2022 ).…”
Section: Bacteria In Gbc Pathogenesismentioning
confidence: 99%